2016
DOI: 10.1002/jcp.25488
|View full text |Cite
|
Sign up to set email alerts
|

Can Cholesterol Metabolism Modulation Affect Brain Function and Behavior?

Abstract: Cholesterol is an important component for cell physiology. It regulates the fluidity of cell membranes and determines the physical and biochemical properties of proteins. In the central nervous system, cholesterol controls synapse formation and function and supports the saltatory conduction of action potential. In recent years, the role of cholesterol in the brain has caught the attention of several research groups since a breakdown of cholesterol metabolism has been associated with different neurodevelopmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 98 publications
0
38
0
Order By: Relevance
“…44 In the brain, cholesterol is either incorporated into the cell membrane, where it regulates signal transduction pathways, or influences synapse formation, action potentials and neurotransmitter release. 45 Furthermore, intracellular cholesterol serves as the precursor for the synthesis of many neurosteroids that are synthesized in the brain, such as allopregnanolone. 45 One of the major ways in which the brain clears cholesterol is via its conversion to 24-(S)-hydroxycholesterol, a reaction catalyzed by the enzyme Cytochrome p450 46A1 (Cyp46A1).…”
Section: Effect Of Bile Acids On Neuronal Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…44 In the brain, cholesterol is either incorporated into the cell membrane, where it regulates signal transduction pathways, or influences synapse formation, action potentials and neurotransmitter release. 45 Furthermore, intracellular cholesterol serves as the precursor for the synthesis of many neurosteroids that are synthesized in the brain, such as allopregnanolone. 45 One of the major ways in which the brain clears cholesterol is via its conversion to 24-(S)-hydroxycholesterol, a reaction catalyzed by the enzyme Cytochrome p450 46A1 (Cyp46A1).…”
Section: Effect Of Bile Acids On Neuronal Dysfunctionmentioning
confidence: 99%
“…45 Furthermore, intracellular cholesterol serves as the precursor for the synthesis of many neurosteroids that are synthesized in the brain, such as allopregnanolone. 45 One of the major ways in which the brain clears cholesterol is via its conversion to 24-(S)-hydroxycholesterol, a reaction catalyzed by the enzyme Cytochrome p450 46A1 (Cyp46A1). 46 24-(S)-hydroxycholesterol is then able to exit the brain and enter the blood stream where it is integrated into the de novo bile acid synthesis pathway in the liver.…”
Section: Effect Of Bile Acids On Neuronal Dysfunctionmentioning
confidence: 99%
“…Many of the post-TBI changes in lipids that have been described involve alterations in blood and brain polyunsaturated fatty acids (PUFA)-containing PLs required for maintaining membrane integrity and synaptogenesis (Liu et al, 2015;Emmerich et al, 2017;Knobloch, 2017;Fiandaca et al, 2018). Lipid associated factors such as cholesterol may be peripherally altered in TBI as, under normal physiological conditions, brain cholesterol is compartmentalized and restricted to the brain by the presence of the blood brain barrier (BBB) (Cartocci et al, 2016); however, BBB disturbances after TBI (Sulhan et al, 2018) may alter the brain's cholesterol content by allowing an exchange between peripheral and CNS cholesterol pools which may in turn adversely affect neuronal function. Studies have shown that CSF cholesterol increases acutely after TBI (Kay et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol is an indispensable building block for all cell membranes and is incorporated in considerable amounts into myelin in the nervous system during the period of rapid brain growth, and it serves as the substrate for the synthesis of bile acids, lipoproteins, vitamin D, hormones, and oxysterols that modulate cholesterol, lipid, and glucose homeostasis [3,9,[17][18][19] . The provision of cholesterol with breastfeeding is associated with higher plasma concentrations of total and low-density lipoprotein cholesterol in breastfed than in formula-fed infants [20] .…”
Section: Cholesterolmentioning
confidence: 99%